Formation of copper oxide II in polymer solution-blow-spun fibers and the successful non-woven ceramic production - Bitencourt da Silva, Alex Nascimento [UNESP]; de Moura, Marcia Regina [UNESP]; Zadorosny, Rafael [UNESP] (Elsevier, 2022)
Copper oxide II is a p-type semiconductor that can be used in several applications. Focusing on producing such material using an easy and low-cost technique, we followed an acetate one-pot-like route for producing a polymer precursor solution with different acetates:PVP (polyvinylpyrrolidone) weight ratios. Then, composite nanofibers were produced using the solution blow spinning (SBS) technique. The ceramic CuO samples were obtained after a calcination process at 600 °C for 2 h, applying a heating rate of 0.5 °C/min. Non-woven fabric-like ceramic samples with average diameters lower than 300 nm were successfully obtained. SEM images show relatively smooth fibers with a granular morphology. XRD shows the formation of randomly oriented grains of CuO. In addition, FTIR and XRD analyses show the CuO formation before the heat treatment. Thus, a chemical reaction sequence was proposed to explain the results.
Keywords: Copper oxide; Nanofibers; Nanowires; Solution blow spinning